ANALISIS DIMENSI YANG MEMBENTUK MOTIVASI SISWA DALAM BELAJAR PADA PROGRAM STUDI ADMINISTRASI PERKANTORAN - Lussianda, Erfa Okta (Kopertis Wilayah X (Sumbar, Riau, Jambi, dan Riau Kepulauan), 2016)
The Purpose of this study is to find at the factors that influence students to choose Office Administrative Study Program at Public Vocational School of Business in Padang. The study was done in SMKN 2 and SMKN 3 Padang. By is an exploratory research. Population was 464 students of grade X, XI, and XII in both SMKN 2 and SMKN 3 with 82 students as sample. Sampling technique was make proportional random sampling. The questionnaire as us to get the data make analysis validity and realiability to check instrument. Analysis was descriptive and factor analysis. The result of this study show 8 factor influence student in choosing Office Administrative in Public Vocational School of Business and Management in Padang ; 1) Ability factor, the total variance is 27,35%. 2) Willingness factor, the total variance is 9,104%. 3) Self Actualization factor, the total variance is 7,047%. 4) Intelligency factor, the total variance is 6,151%. 5) interest factor, the total variance is 5,453%. 6) target factor, the total variance is 5,179%. 7) Creativity in studying factor, the total variance is 4,425%. 8) Self Esteem factor, the total variance is 3,961%. Based on those factors, total accumulative factor is 68,455%.Key word : Motivation of Achievement, Motivatiaon Study, Office Administrative Scope